2021
DOI: 10.1123/ijspp.2020-0844
|View full text |Cite
|
Sign up to set email alerts
|

Continuous Versus Intermittent Running: Acute Performance Decrement and Training Load

Abstract: Purpose: To examine the effect of continuous (CON) and intermittent (INT) running training sessions of different durations and intensities on subsequent performance and calculated training load (TL). Methods: Runners (N = 11) performed a 1500-m time trial as a baseline and after completing 4 different running training sessions. The training sessions were performed in a randomized order and were either maximal for 10 minutes (10CON and 10INT) or submaximal for 25 minutes (25CON and 25INT). An acute performance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 32 publications
1
4
0
Order By: Relevance
“…When we examined experimentally the underpinning of the model, which relates a training dose to its fatigue or APD element, our findings suggested that commonly used TL metrics do not quantify the training dose effectively. 3,16,20 Although we agree with our colleagues that these findings may not directly challenge the validity of the TL concept, they do question the validity of the TL metrics evaluated-when TL is conceptualized as a training dose. The validity of TL metrics as a representation of the training dose remains untested.…”
supporting
confidence: 68%
“…When we examined experimentally the underpinning of the model, which relates a training dose to its fatigue or APD element, our findings suggested that commonly used TL metrics do not quantify the training dose effectively. 3,16,20 Although we agree with our colleagues that these findings may not directly challenge the validity of the TL concept, they do question the validity of the TL metrics evaluated-when TL is conceptualized as a training dose. The validity of TL metrics as a representation of the training dose remains untested.…”
supporting
confidence: 68%
“…The NASA Task Load Index has been little used in the context of sport monitoring but showed good agreement with the APD observed following cycling sessions 9 ; it performed better than other TL metrics in the variable intensity running study. 10 Although sRPE contradicts APD, we have found end-exercise RPE scores to show good agreement with APD when measured both as TT 10 and TTF. 8 In the latter study, we reported a strong correlation for minute ventilation ( VE ), recorded at the end of exercise, with subsequent TTF.…”
Section: Practical Applicationsmentioning
confidence: 59%
“…The relationship between exercise intensity and athlete stress is inherently nonlinear and some TL metrics attempt to account for this. 12,21,22 However, reasonable agreement with APD was still not found 9,10 and may be confounded by the influence of the structure of the training session. 29,32,33 Accordingly, further research may be required to determine how TL metrics can capture and present information on session structure by, for example, exploring methods such as exposure variation analysis.…”
Section: Practical Applicationsmentioning
confidence: 98%
See 2 more Smart Citations